Status Stok dan Pengelolaan Berkelanjutan Ikan Selar (Selar boops Cuvier, 1833.) di WPPRI 713 Berdasarkan Analisis Surplus Produksi - Wayan Kantun; Hernita Hernita (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Teknologi dan Bisnis Maritim Balik Diwa, 2025)
Fundamental problems in managing oxeye scad fisheries in WPPRI 713 include limited comprehensive stock data, resulting in suboptimal resource utilization and potential unsustainability. This study aims to estimate the sustainable potential, utilization rate, optimum effort, and allowable catch as the basis for sustainable oxeye scad fisheries management. This study uses a quantitative approach based on statistical data for ten years (2015–2024), analyzed using the Schaefer surplus production model. The results indicate that the sustainable potential of oxeye scad reaches 63,404,117 tons/year, the utilization rate is 18.99%, the optimum effort is 3,730,925 units, and the allowable catch is 50,723 tons/year. These results confirm that oxeye scad stocks are in a productive condition and opportunities for utilization development are still wide open, but still require management control through regulation of fishing effort and the implementation of quotas based on the allowable catch. In conclusion, oxeye scad fisheries in WPPRI 713 can still be developed safely while adhering to established biological limits